Antibacterial activity of herbal preparation –Agnijith - Karthiha N,; Gayathri Devi S, (International Journal of Phytomedicine, 2015)
“Agnijith” a herbal preparation was evaluated against fifteen different microorganisms at different concentrations 120mg, 130mg, 150mg, 170mg and 190mg/100mg. Chloromphenicol was used as control. The in vitro antibacterial activity was performed by agar well diffusion method and minimum inhibitory concentration (MIC) method. “Agnijith” was found to be more potent in inhibiting the microorganisms such as Bacillus subtilis, Klebsiella pneumoniae, Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Pseudomonas flourescence, Proteus mirabilis and Shigella dysentriae, whereas no inhibition zone was found against Micrococcus luteus, Streptococcus pyrogens, Enterococcus faecalis, Proteus vulgaris and Salmonella typhimurium by well diffusion method. The zone of inhibition ranges from 12mm to 25mm. Bacillus subtilis, Klebsiella pneumoniae, Staphylococcus aureus, Pseudomonas aeruginosa, Pseudomonas flourescence, Shigella dysentriae were found to be sensitive at various concentrations by minimum inhibitory concentration method. The results clearly demonstrates that the “Agnijith” to be an effective antibacterial agent and could be used to treat diseases caused by microorganisms.